"Appily ever after": how to create your own library mobile app through easy to use, low cost technology. Issue 10 (4th December 2017) - Boller, Susan
Abstract : Purpose: The purpose of this paper is to demonstrate that library staff can develop their own mobile app without having significant technology experience by using existing, easily accessible low-cost programs. Smart phones and tablets are here to stay. Libraries need to embrace this trend by developing mobile apps to encourage reading and provide access to resources that are safe and educational. It is about putting technology at the service of reading. Susan Boller and Marie-Pierre Preece, librarians at Les Marronniers Primary School at the International School of Geneva, received wide recognition when they were awarded the 2016 ALA Presidential Citation for Innovative International Library Projects for their mobile application "Marronniers Library". Design/methodology/approach: The search to develop a mobile application was challenging. "The process was long and complex, as we had a very small budget and no particular expertise in information technology". While researching the best way to develop an app for her library, Susan Boller explored a wide range of options with differing costs ranging from a few hundred dollars to over 20, 000 (for a custom-built app). Findings: It is feasible for a school library with limited resources to develop its own mobile application. The library staff can develop such an app without having significant technology experience by using existing easily accessible low-cost programs. Developing and maintaining such an app do not require specialist IT knowledge, and these can be done internally by people interested in technology. The app is good value. The annual cost, excluding subscriptions to databases, is approximately 400. Such an app is well sustainable. The chosen platform is flexible and allows the content to be continuously maintained and updated internally at any moment without additional cost. Originality/value: Having been awarded the 2016 ALA Presidential Citation for Innovative International Library Projects demonstrates the originality of the author's "Marronniers Library" mobile application. It is, to the best of the author's knowledge, the only one of its kind in a primary school library.